Full Endoscopic Surgery of Bullet Removal of The Spine: A Case Report - Wildan Malik; Nugroho Setyowardoyo (Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: In the past decade, the endoscopic technique has been applied as a feasible and less invasive approach to orthopedic surgeries. Minimally invasive, full-endoscopic surgery has gained considerable attention in managing air gun injuries to the spine. Sacrum injuries among air gun wounds are rare and few have been published in case reports. Here, we present the management of air gun-bullet injury to the pediatric spinal spine in a 5-year-old child using endoscopic surgical intervention.Case Report: A 5-year-old girl was accidentally shot in the lower back with an air gun. The CT scan imaging shown a retained projectile in the pedicle of S1 vertebrae without vascular injury or unstable vertebral fracture. A minimally invasive, full-endoscopic surgical technique was applied to remove the bullet in this patient. On post-surgical follow-up, the patient was in a good recovery state.Discussion: Surgical intervention is needed for decompression, stabilization, and diminished risks of lead toxicity. The percutaneous endoscopic approach is the least invasive intervention performed to ensure a targeted approach through the anatomical openings of the spine and through intervertebral discs and bone structures, thereby further reducing spinal instability, blood loss, and infection risk.Conclusion: The endoscopic operation of minimally invasive surgical techniques is an effective operative approach not only limited in spinal stenosis cases, but also in air gun injuries.